Explorando la relación entre el aprendizaje autorregulado y el rendimiento académico en el aprendizaje de inglés entre estudiantes de secundaria en Bogotá (2024)
Effective self-regulated learning strategies have been identified as a critical factor influencing academic performance, particularly in the context of language learning. This study aimed to explore the relationship between self-regulation skills and academic achievement among 13 secondary school students in Bogotá, Colombia, who were learning English as a foreign language. A mixed-methods approach was employed, collecting quantitative data from questionaries, self-assessments, and academic reports, as well as qualitative insights through student interviews. The findings revealed a significant positive correlation between the use of self-regulated learning strategies and academic performance. Students who demonstrated proficiency in goal-setting, planning, self-monitoring, and self-evaluation techniques achieved higher grades, pass rates, and mastery in specific knowledge areas such as grammar and oral expression. Furthermore, the interplay between metacognition, cognitive skills, and motivational factors emerged as a crucial determinant of academic success. Students with strong cognitive abilities coupled with effective self-regulation strategies exhibited a distinct advantage in learning and classroom performance. The study also highlighted the pivotal role of intrinsic motivation and engagement in driving the effective application of self-regulation strategies. Students who displayed higher levels of interest, commitment, and appreciation for the value of learning English were more likely to employ self-regulated learning approaches, ultimately leading to better academic performance. Based on these findings, the study emphasizes the need for comprehensive pedagogical interventions that holistically address self-regulation skills, (meta)cognitive development, and motivational factors. Recommendations include explicit instruction in self-regulated learning strategies, integration of metacognitive practices, fostering intrinsic motivation, tailored cognitive support, continuous assessment and feedback, collaborative learning opportunities, and ongoing professional development for educators. Ultimately, this research underscores the importance of equipping students with self-regulation abilities, enabling them to take an active, strategic approach to their learning journey and maximizing their academic potential in language learning and beyond.